A General Class of Derivative Free Optimal Root Finding Methods Based on Rational Interpolation - Fiza Zafar; Nusrat Yasmin; Saima Akram; Moin-ud-Din Junjua (The Scientific World Journal)
We construct a new general class of derivative free n-point iterative methods of optimal order of convergence 2n-1 using rational interpolant. The special cases of this class are obtained. These methods do not need Newton’s iterate in the first step of their iterative schemes. Numerical computations are presented to show that the new methods are efficient and can be seen as better alternates.